2023
DOI: 10.1183/23120541.00656-2022
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting lung oscillometry results: Z-scores or fixed cut-off values?

Abstract: Instead of using % predicted values or Z-scores to define and quantify respiratory abnormality in oscillometry, fixed cut-off values will likely give more accurate discrimination https://bit.ly/3vVmIyE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…While numerous reference equations exist globally, none has covered such a broad age range. Interestingly, the authors also provide cut-off values for IOS indices, which is in line with the proposition that in comparison to predicted values or z-scores, fixed cut-off values will be more accurate to discriminate between normal and abnormal oscillometric outcomes in adults, with a reasonably good sensitivity, specificity and overall accuracy [ 2 ]. Aligning with current expectations, the authors incorporated sex, height, age and body mass index as key physiological variables into their reference equation.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…While numerous reference equations exist globally, none has covered such a broad age range. Interestingly, the authors also provide cut-off values for IOS indices, which is in line with the proposition that in comparison to predicted values or z-scores, fixed cut-off values will be more accurate to discriminate between normal and abnormal oscillometric outcomes in adults, with a reasonably good sensitivity, specificity and overall accuracy [ 2 ]. Aligning with current expectations, the authors incorporated sex, height, age and body mass index as key physiological variables into their reference equation.…”
mentioning
confidence: 55%
“…The only variable that needs to be measured to interpret oscillometry indices seems to be height. Our previous assertion that interpreting oscillometry necessitates only the use of cut-off values rather than reference values aligns seamlessly with this notion [ 2 ].…”
mentioning
confidence: 93%
“…We previously reported that fixed cutoff values may provide better sensitivity, specificity, positive predictive value, and negative predictive value to differentiate between normal and abnormal findings on oscillometry, and we have argued that fixed cutoff values (such as those used for hypertension and diabetes) should be the way forward ( 5 ). In the past, many authors have pragmatically used fixed cutoff values to differentiate between normal and abnormal oscillometry results ( 6 ).…”
mentioning
confidence: 99%